Understanding the adaptation strategies of Canadian Olympic athletes using archival data - Schinke, R. J.; Battochio, R. C.; Dubuc, N. G.; Swords, S.; Apolloni, G.; Tenenbaum, G. (Journal of Clinical Sport Psychology, 2008)
Athletes employ a variety of adaptation strategies when adjusting to competitive environments. Fiske (2004) identified five core motives that facilitate human adaptation: (a) understanding, (b) controlling, (c) self-enhancement, (d) belonging, and (e) trusting. Recent qualitative analyses (Schinke, Gauthier, Dubuc, & Crowder, 2007) revealed that these motives correspond to particular adaptation strategies that professional athletes employ in stressful settings. The present study uses analysis of archival data (i.e., journalistic accounts) to explore the adaptation efforts of Canadian Olympic athletes (N = 103) as they prepared for and participated in summer (n = 35) and winter (n = 68) games. Contextual experts with extensive Olympic experience were enlisted to clarify the archival record. Findings revealed that the Olympic athletes used strategies corresponding to each of Fiske's five motives, as well as numerous specific substrategies. Use of substrategies was consistent across athletes, regardless of Olympic experience, gender, or season (e.g., winter or summer games). Discussion explores the implications of adaptation strategies for Olympic athletes and their supporting staff.